Travel experience on social media: the impact towards tourist destination choice / Noraihan Mohamad, Vivien Tan and Pei Pei Tan - Mohamad, Noraihan; Tan, Vivien; Tan, Pei Pei (Research Management Institute (RMI), 2022)
Social media has changed the way travellers see and experience their trips. It creates opportunities for travellers to search for useful travel information, choose destinations and also shares their travel experiences. The aim of this study is to investigate the influence of positive and negative experiences shared on social media as well as subjective norms towards tourists' decisions on destination choice by adapting the Theory of Planned Behaviour (TPB). Based on a cross-sectional design, self-administered questionnaires were distributed to local tourists in Klang Valley, Malaysia. A total of 340 respondents were accessed based on the convenience sampling technique. The Multiple Linear Regression technique analysis was employed to test the research hypotheses. The results revealed positive experiences shared on social media and subjective norms perform as important predictors to explain tourists' behavioural intention to visit a certain destination. In conclusion, this study provides valuable information to destination management organisations in terms of social media management in the development of strategic plans to increase tourists' behavioural intention.